Assessment of knowledge, attitudes, and practices regarding microbiota composition and influencing factors among the general population in Jazan province: A cross-sectional study (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The human gut microbiota is crucial to maintaining health and preventing diseases. The general population‘s knowledge, attitudes, and practices regarding microbiota composition and the factors affecting it remain poorly understood in Saudi Arabia. The present cross-sectional study aimed to evaluate the level of knowledge, attitudes, and practices among the general population in the Jazan Province of Saudi Arabia regarding the gut microbiota and its main influencing factors. Materials and Methods: A descriptive, cross-sectional design was employed, utilizing a validated self-administered online questionnaire to collect data from participants aged 18 years and older. The study population excluded nonresidents of the Jazan region, individuals below 18, and those who declined to participate. Nonrandomized convenience sampling was used to recruit participants from the Jazan Province, targeting the general population. Results: One thousand one hundred twenty-six participants completed the survey, resulting in a response rate of 93%. Most participants (50.4%) had average microbiota knowledge, 14.7% demonstrated good understanding, and 34.9% had poor knowledge. Regarding probiotics, the findings indicated that 76.4% of participants exhibited insufficient knowledge, 21.1% had average knowledge, and 2.5% displayed good knowledge. Most participants (65.7%) held a neutral attitude toward antibiotics and probiotics. Conclusion: This study highlights a significant gap in understanding probiotics among the general population in the Jazan Region. Comprehensive education and awareness campaigns are urgently needed to promote a better understanding of microbiota composition, its significance for health, and the potential benefits of probiotics. Effective public health initiatives should be developed to provide accurate and up-to-date probiotic information, fostering positive health outcomes.J. Adv. Vet. Anim. Res., 10(4): 773–781, December 2023http://doi.org/10.5455/javar.2023.j733